IMMUNOBIOLOGICAL PROPERTIES OF LUMPY SKIN DISEASE VIRUS STRAIN LSD CATTLE/DAGESTAN/2015 - S. V. Kononova; O. P. Byadovskaya; A. V. Kononov; I. N. Shumilova; E. E. Artyukhova (Ветеринария сегодня)
Data on the study of immunobiological properties of a novel lumpy skin disease virus strain LSD Cattle/Dagestan/2015 are presented in the paper. In the course of the research it was found that the obtained strain is biologically active, free from contamination with foreign biological agents. It is type specific and with its immunobiological characteristics meets the standards and requirements set before virus strains used for vaccine and diagnostic production.